The Discovery Learning in Teaching Writing Skill in Junior High School - Retika Wista Anggraini (Universitas Indo Global Mandiri, 2020)
ABSTRACTDescriptive writing is a one of genre taught in the year VII students of Junior High School based on Curriculum 2013. In writing descriptive, it is expected to the students are able to write a simple descriptive. Therefore through descriptive writing, the writer would like to minimize the students learning problem, to know the students achievements and their difficulties in learning writing. In 2013 English curriculum, there are four language skills that must be taught to Junior High School students, those are reading, listening, speaking, and writing. Oshima and Haque (1999:50) state that descriptive writing appeals to the senses, so it tells how something looks, feel, smells, tastes and sounds. Briefly, descriptive writing is used to make something clear and vivid, so that the readers can understand it. The teaching of English based on School Based Curriculum in Indonesia is delivered through text and context. Literary works are part of the text. They have been taught for all level of schools in Indonesia. Whether the subject is listening, speaking, reading, or writing, teachers of English should deliver it through text and context. Consequently, discovery learning refers to various instructional design models that engage students in learning through discovery. Discovery learning is a technique of inquiry-based learning and is considered a constructivist based approach to education. It is supported by the work of learning theorists and psychologists (Jerome Bruner, 1960). Commonly, seventh grade students of SMP Negeri 10 Palembang are afraid of making mistakes and worried about their ability in choosing and arranging words to produce sentences. Those feelings seem to make the students unconfident in a writing class. The Discovery learning technique tries to improve students’ writing skill and make the students more active in the class because it contains some activities that encourage the students to write up in the class.Keywords : Writing, Descriptive Writing, Discovery Learning, English Curriculum, Literary Works ABSTRAK Penulisan deskriptif adalah salah satu genre yang diajarkan pada siswa kelas VII SMP berdasarkan Kurikulum 2013. Dalam menulis deskriptif, diharapkan siswa mampu menulis deskriptif sederhana. Oleh karena itu melalui penulisan deskriptif, penulis ingin meminimalkan masalah belajar siswa, untuk mengetahui prestasi siswa dan kesulitan mereka dalam belajar menulis. Dalam kurikulum Bahasa Inggris 2013, ada empat keterampilan bahasa yang harus diajarkan kepada siswa SMP, yaitu membaca, mendengarkan, berbicara, dan menulis. Oshima dan Haque (1999: 50) menyatakan bahwa penulisan deskriptif menarik bagi indera, sehingga ia menceritakan bagaimana sesuatu terlihat, dirasakan, tercium, terasa, dan terdengar. Secara singkat, penulisan deskriptif digunakan untuk membuat sesuatu menjadi jelas dan jelas, sehingga pembaca dapat memahaminya. Pengajaran Bahasa Inggris berdasarkan Kurikulum Berbasis Sekolah di Indonesia disampaikan melalui teks dan konteks. Karya sastra adalah bagian dari teks. Mereka telah diajarkan untuk semua tingkatan sekolah di Indonesia. Apakah subjeknya mendengarkan, berbicara, membaca, atau menulis, guru bahasa Inggris harus menyampaikannya melalui teks dan konteks. Akibatnya, belajar penemuan mengacu pada berbagai model desain pembelajaran yang melibatkan siswa dalam belajar melalui penemuan. Belajar Penemuan adalah teknik pembelajaran berbasis inkuiri dan dianggap sebagai pendekatan berbasis konstruktivis terhadap pendidikan. Ini didukung oleh karya belajar teori dan psikolog (Jerome Bruner, 1960). Umumnya, siswa kelas tujuh SMP Negeri 10 Palembang takut membuat kesalahan dan khawatir tentang kemampuan mereka dalam memilih dan mengatur kata-kata untuk menghasilkan kalimat. Perasaan itu membuat siswa tidak percaya diri dalam suatu kegiatan menulis. Teknik belajar penemuan memberikan keterampilan menulis bagi siswa di SMP Negeri 10 Palembang dengan meningkatkan keterampilan menulis dan membuat siswa lebih aktif di kelas karena ada beberapa kegiatan yang mendorong siswa untuk menulis di kelas.Kata kunci: Menulis, Menulis Deskriptif, Belajar Penemuan, Kurikulum Bahasa Inggris, Karya Sastra